2021
DOI: 10.7759/cureus.18165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Asynchronous Spaced Education Learning Intervention on Emergency Medicine Clinician Opioid Prescribing

Abstract: Barrett et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Furthermore, this approach promotes high learner engagement with sustained knowledge acquisition. 17 Although additional education remains an important opportunity to increase nursing participation in AMS, another major barrier is prescriber pushback and challenges with interdisciplinary communication. 23 One participant in our study stated, "Nurses are not the ones deciding on when to start antibiotics or which [antibiotics] to use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this approach promotes high learner engagement with sustained knowledge acquisition. 17 Although additional education remains an important opportunity to increase nursing participation in AMS, another major barrier is prescriber pushback and challenges with interdisciplinary communication. 23 One participant in our study stated, "Nurses are not the ones deciding on when to start antibiotics or which [antibiotics] to use.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not assess whether our intervention led to meaningful changes in clinical practice, though research has previously demonstrated changes in clinical practice following spaced education interventions. [24][25][26][27] In this pilot study, we focused on the implementation and utility of the QuizTime platform for AMS education. Future efforts could focus on improving participation, assessing long-term impact, and scaling similar interventions to a broader population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between spaced education through multiple-choice questions and improvements in clinical performance is not new. Shaw et al 6 demonstrated that primary care clinicians who received spaced education self-reported substantially more clinical practice change than those who received only standard didactics, and Barrett et al 28 showed a change among emergency department clinicians who received training with QuizTime. Kerfoot et al 19 reported that spaced education improved clinical behaviors related to prostate cancer screening in a trial of 95 primary care clinicians.…”
Section: Discussionmentioning
confidence: 99%
“… 11 The combination of spaced education and retrieval practice can be better than traditional pedagogical approaches for clinicians, with evidence suggesting improved knowledge acquisition, knowledge retention, and, in some cases, clinical practice. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 The combination of spaced education and retrieval practice also has the potential for deployment at the institutional level for large learner groups. Whether spaced education with retrieval practice can change prescribing patterns at the institutional level is unknown.…”
Section: Introductionmentioning
confidence: 99%